Statics and Dynamics of Magnetocapillary Bonds - Lagubeau, G (American Physical Society, 2016)
When ferromagnetic particles are suspended at an interface under magnetic fields, dipole-dipole interactions compete with capillary attraction. This combination of forces has recently given promising results towards controllable self-assemblies as well as low-Reynolds-number swimming systems. The elementary unit of these assemblies is a pair of particles. Although equilibrium properties of this interaction are well described, the dynamics remain unclear. In this paper, the properties of magnetocapillary bonds are determined by probing them with magnetic perturbations. Two deformation modes are evidenced and discussed. These modes exhibit resonances whose frequencies can be detuned to generate nonreciprocal motion. A model is proposed that can become the basis for elaborate collective behaviors. © 2016 American Physical Society.